(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One important soil parameter that is measured in many engineering, geology, soil and environmental science investigations is the soil water content (θ). For example, θ influences the assessment of soil strength, hydraulic conductivity, groundwater recharge, and soil aeration condition. Measurement of θ is essential for tracking and managing a number of soil processes. A quick and non-destructive method for determining μ in soils with drastically different compositions is the gammaray attenuation (GRA) approach. However, lab physics classes rarely cover GRA. An experiment involving the measurement of θ using a teaching GRA apparatus is proposed. A Geiger-Müller detector, a radiation counter, and a radioactive source with a 37Cs decay were the components of the experimental setup. Four different granulometric compositions of soil samples were examined. The transmitted gamma-ray photon intensity and θ were found to have strong linear relationships (correlation coefficients ranging from −0.95 to −0.98). There were variations in the soil porosity between the traditional and GRA techniques, ranging from around 7.8% to about 18.2%. Furthermore, a robust linear correlation (correlation coefficients ranging from 0.90 to 0.98) was noted between the GRA and the conventional gravimetric technique for measuring θ. The effectiveness of the teaching GRA apparatus in measuring θ was confirmed. Additionally, the device enables undergraduate students from a variety of subject areas to be introduced to a few significant facets of the study of contemporary physics.